Everyday life of high school students at university lyceum and gymnasium: Outcomes of comparative research - Sergey D. Polyakov; Liliya A. Belozеrova; Valeria V. Vershinina (Saratov State University, 2023)
The study appears to be relevant since it addresses the research gap in the question how the way school life is organized influences students' perception of various aspects of everyday life at school. Notably, the subject of this research is not the objective facts of school everyday life, but their representation in the minds, opinions, and assessments of high school students. The article suggests the model of school everyday life as a research object; this model is based on the investigation of various approaches to the analysis of everyday life (socio-anthropological, socio-psychological, socio-pedagogical). The goal of the study is to identify the influence external organization of school life has on the peculiarities of senior high schoolers' everyday life. The hypothesis of the study is as follows: The forms of school life organization as well as the specifics of the school community are reflected in the importance of the topics students discuss outside the classroom, their "attachment" to the functional tools of the Internet, and the prevalence of Internet slang and obscene language in the speech of tenth-graders. The participants were the tenth-grade students (N = 143) of the gymnasium (n = 75) and the lyceum (n = 68) (the city of Ulyanovsk) aged from 16 to 17 years. The following methodswere used: "The Circles Test" (Thomas J. Cottle) was used to determine the characteristics of school time perception; "The Test of Color Relations" (A. M. Etkind, N. M. Platonova) was used to fix the parameters of the socio-physical space of school everyday life; a questionnaire was utilized to identify the main demographic characteristics and characteristics of the personalized material "world" of school everyday life. The results of the research are as follows: Tenth-graders' past school experience influences the personal value of the "school past, present and future"; The perception of the physical space of an educational organization depends on its "appropriation" and psychological safety of use; The data are presented on the differences in the content and styles of high schoolers' communication outside of the classroom depending on the characteristics of their educational organizations; Tenth-graders' attitude towards the norms of "a school look" as well as the use of gadgets is shown to be linked to the extent to which "school behavior" is regulated in their educational organization. The article concludes that the form of school life organization is a factor influencing some characteristics of the everyday life of senior high schoolers. The study emphasizes the practical application of further research on the issues of interest.